Microstructural evolution of GH4079 superalloy during hot deformation and heat treatment - Wenwen Zhang; Xingang Liu; Tonggang Lu; Yunlong Liu; Ying Guo; Heyong Qin; Qiang Tian (Journal of Materials Research and Technology)
Through hot compression and subsequent heat treatment experiments on GH4079 superalloy, the influence of different hot deformation and heat treatment conditions on the evolution of GH4079 superalloy microstructure was studied. The evolution of grains and γ′ phases under different thermomechanical conditions was investigated. The results indicate that at deformation temperatures above 1100 °C and strain rates ranging from 0.01 to 0.1 s−1, the primary mechanism of dynamic softening in the alloy is discontinuous dynamic recrystallization (DDRX). When the deformation temperature is below 1100 °C and strain rates range from 0.01 to 0.1 s−1, both continuous dynamic recrystallization (CDRX) and DDRX are the main dynamic softening mechanisms. Due to high strain energy accumulation, the samples deformed at lower temperatures (below 1100 °C) and then solution-treated at 1120 °C for 8 h exhibit significant increases in recrystallization volume fraction and recrystallization grain size. Conversely, the samples deformed at higher temperatures (above 1100 °C) and then solution-treated at 1120 °C for 8 h show minimal changes in recrystallization volume fraction and recrystallization grain size. After solution treatment at 1140 °C, the grain size of the alloy significantly increases. The samples deformed at higher strain rates exhibit the evolution of fine γ′ phases into elongated rod shapes during solution treatment, while larger γ′ phases undergo splitting processes.